Hydroxyl-anchored covalent organic crown-based polymers for CO2 fixation into cyclic carbonates under mild conditions. Issue 1 (6th December 2021) - Hao, Yongjing; Yan, Xiuli; Chang, Tao; Liu, Xiaohuan; Kang, Lianwei; Zhu, Zheng; Panchal, Balaji; Qin, Shenjun
Abstract : A series of covalent organic crown-based polymers coordinated with KI exhibit high activity. The synergetic effect plays an important role in accelerating the reaction rate. Abstract : Covalent organic polymers (COPs) are a kind of promising material for carbon dioxide (CO2 ) reutilization. Herein, a series of covalent organic crown-based polymers (COCP–H, COCP–OH, COCP–CH3, COCP–Bu, COCP–NH2 ) were designed and synthesized. These synthesized COCPs were characterized by FT-IR, SEM, BET and 13 C CP MAS NMR. Notably, the novel COCP–OH catalyst with hydroxyl and crown ether groups on the framework simultaneously was particularly effective in cycloaddition reactions, giving a cyclic carbonate yield of 94.8% after 24 h at 70 °C with 1 bar of CO2, using 0.0735 mmol of KI and 71 mg of COCP–OH. It is worth considering that there is a synergetic effect between the hydroxyl group and KI activated by the crown ether fragment, which plays a crucial role in accelerating the reaction rate. The coordinated interaction of crown ether with KI was also confirmed by X-ray photoelectron spectroscopy (XPS). Thus, this study provides a new approach to fabricate multifunctional COP materials for the coupling reaction of CO2 under mild conditions.